2012
DOI: 10.3168/jds.2011-5284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of d-cloprostenol dose and corpus luteum age on ovulation, luteal function, and morphology in nonlactating dairy cows with early corpora lutea

Abstract: Luteolysis is a key event in cattle reproduction. A standard dose of exogenous PGF(2α) will induce full luteolysis in the majority of cows with a matured corpus luteum (CL). However, this will not occur in cows with a CL <5d old. To date, it is not known whether a larger dose will have a more potent luteolytic effect in cows during early diestrus. The objective of this study was to characterize the effect of 2 doses of d-cloprostenol (150 and 300 μg) on the progesterone concentration, luteal diameter, and ovul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…A superior luteolytic effect of a double dose of d‐CLO was also shown in cows treated at early stages of the oestrus cycle (Valldecabres‐Torres et al. ). A similar study also found a superior luteolytic response in mares treated with higher doses of PGF at early stages of the oestrus cycle (Cuervo‐Arango and Newcombe ).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…A superior luteolytic effect of a double dose of d‐CLO was also shown in cows treated at early stages of the oestrus cycle (Valldecabres‐Torres et al. ). A similar study also found a superior luteolytic response in mares treated with higher doses of PGF at early stages of the oestrus cycle (Cuervo‐Arango and Newcombe ).…”
Section: Discussionmentioning
confidence: 86%
“…; Valldecabres‐Torres et al. ). However, in cows from Experiment II, the presence of an older CL at the time of PGF treatment appeared to override the luteolytic resistance of the younger accessory CL.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations